Observations of moose behaviour and foraging choices in summer - Spitzer, Robert; Ericson, Monica; Felton, Annika M.; Heim, Morten; Raubenheimer, David; Solberg, Erling J.; Wam, Hilde K.; Rolandsen, Christer M. (Zenodo, 2024)
Understanding how the nutritional properties of food resources drive foraging choices is important for the management and conservation of wildlife populations. For moose ( Alces alces ), recent experimental and observational studies during the winter have shown macronutrient balancing between available protein (AP) and highly metabolizable macronutrients (total non-structural carbohydrates [TNC] and lipids). Here, we combined the use of continuous-recording camera collars with plant nutrient analyses and forage availability measurements to obtain a detailed insight into the food and nutritional choices of three wild moose in Norway over a five-day period in summer. We found that moose derived their macronutrient energy primarily from carbohydrates (74.2%), followed by protein (13.1%), and lipids (12.7%). Diets were dominated by deciduous tree browse (71%). Willows ( Salix spp.) were selected for and constituted 51% of the average diet. Moose consumed 25 different food items during the study period of which nine comprised 95% of the diet. Moose tightly regulated their intake of protein to highly metabolizable macronutrients (AP:TNC+lipids). They did this by feeding on foods that most closely matched the target macronutrient ratio such as Salix spp., or by combining nutritionally imbalanced foods (complementary feeding) in a non-random manner that minimized deviations from the intake target. The observed patterns of macronutrient balancing aligned well with the findings of winter studies. Differential feeding on nutritionally balanced downy birch ( Betula pubescens ) leaves versus imbalanced twigs+leaves across moose individuals indicated that macronutrient balancing may occur on as fine a scale as foraging bites on a single plant species. Utilized forages generally met the suggested requirement thresholds for the minerals calcium, phosphorus, copper, molybdenum, and magnesium but tended to be low in sodium. Our findings offer new insights into the foraging behavior of a model species in ungulate nutritional ...